Training on Calculation of Production Cost and Determination of Product Selling Price to Increase Competitiveness of MSMEs in Alai Village - Marshelindy, Marshelindy; Handayani, Susi; Emilda, Emilda; Ratu, Mutiara Kemala; Mutaqin, Zenal (Pascasarjana Universitas Mataram, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, including in job creation, improving people's welfare, and strengthening the national economic structure. One effective solution to address these challenges is through training on cost of goods produced (COGS) calculation and selling price determination. This study focuses on the training provided to MSMEs in Alai Village, with the aim of improving the understanding of business actors regarding the components of COGS and effective selling price setting strategies. The method used in this research is the field practice method which goes through three stages, namely preparation, implementation and evaluation. The results showed that participants gained better knowledge about COGS calculations and were able to set competitive selling prices, thereby increasing operational efficiency and profit margins. This was proven when researchers conducted periodic research at 2 stages, namely before the presentation of the material (pretest) and after the presentation of the material (posttest). Thus, this training makes a positive contribution to business sustainability and the economic welfare of local communities, increases the competitiveness of MSMEs, and has a positive impact on local economic growth